Combined Induction of Rubber-Hand Illusion and Out-of-Body Experiences - Olivé, Isadora; Berthoz, Alain (Frontiers in Psychology, 2012)
The emergence of self-consciousness depends on several processes: those of body ownership, attributing self-identity to the body, and those of self-location, localizing our sense of self. Studies of phenomena like the rubber-hand illusion (RHi) and out-of-body experience (OBE) investigate these processes, respectively for representations of a body-part and the full-body. It is supposed that RHi only target processes related to body-part representations, while OBE only relates to full-body representations. The fundamental question whether the body-part and the full-body illusions relate to each other is nevertheless insufficiently investigated. In search for a link between body-part and full-body illusions in the brain we developed a behavioral task combining adapted versions of the RHi and OBE. Furthermore, for the investigation of this putative link we investigated the role of sensory and motor cues. We established a spatial dissociation between visual and proprioceptive feedback of a hand perceived through virtual reality in rest or action. Two experimental measures were introduced: one for the body-part illusion, the proprioceptive drift of the perceived localization of the hand, and one for the full-body illusion, the shift in subjective-straight-ahead (SSA). In the rest and action conditions it was observed that the proprioceptive drift of the left hand and the shift in SSA toward the manipulation side are equivalent. The combined effect was dependent on the manipulation of the visual representation of body parts, rejecting any main or even modulatory role for relevant motor programs. Our study demonstrates for the first time that there is a systematic relationship between the body-part illusion and the full-body illusion, as shown by our measures. This suggests a link between the representations in the brain of a body-part and the full-body, and consequently a common mechanism underpinning both forms of ownership and self-location.